PEMBUATAN VIDEO EDUKASI SEBAGAI UPAYA MENINGKATKAN KESADARAN MAHASISWA SISTEM INFORMASI DI UNIVERSITAS INTERNASIONAL BATAM TERHADAP BERITA PALSU DI ERA DIGITAL - Hanif Permadi Diny; Diny Anggriani Adnas; Deli Deli (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
This research aims to explore the impact of fake news and the effectiveness of making educational videos as an effort to increase awareness of information systems students at Batam International University regarding fake news in the digital era. Through a survey method using a questionnaire distributed to students from the 2021 to 2024 class, this research identified the level of understanding and awareness of students regarding the dangers of fake news before and after showing educational videos. The research results showed that 98% of respondents felt that the videos presented were interesting and easy to understand, and suited their needs, which indicates that visual media can be an effective tool in conveying information. In addition, data analysis shows that increasing digital literacy among students contributes to their ability to recognize and verify information, thereby reducing the risk of spreading hoaxes.